Interleukin-1 as a Predictor Cytokine SARS-CoV: Article Review - Lisa Savitri; Elfred Rinaldo Kasimo; Rochmad Krissanjaya; Syntia Tanu Juwita; Ester Lianawati Antoro; Ida Septika Wulansari (Biology, Medicine, & Natural Product Chemistry, 2023)
Severe acute respiratory syndrome coronavirus (SARS-CoV) is an etiologic agent of respiratory disease that has a mortality rate of 10%. IL-1 actively participates in the inflammatory response to infection. SARS-CoV-2 appears to act on the activation and maturation of IL-1?, which in turn activates other proinflammatory cytokines, such as IL-6 and TNF-. Therefore, IL-1? is part of the cytokine storm generated by coronavirus infection. Elevated levels of the IL-1 receptor antagonist (IL-1Ra) in severe cases of COVID-19, and this marker have been associated with increased viral load, loss of lung function, lung damage, and risk of death. In addition, there is an increase in IL-1? levels in patients with severe COVID-19, and this is strongly associated with lung injury. IL-1 levels are associated with the virulence of the process, and significantly higher serum levels have been observed in severe symptomatic SARS-CoV-2 cases than in mild cases or in those infected with the 2003 SARS-CoV coronavirus or 2012 MERS coronavirus.